Pengaruh Jumlah Instrumen Investasi, Harga Emas, Nilai Kurs Rupiah dan Biaya Penyelenggaraan Ibadah Haji terhadap Hasil Investasi Keuangan Haji di Indonesia - Agung Kurnia Setiawan; Nafis Irkhami (Universitas Muhammadiyah Surabaya, 2023)
Abstract This research aims to analyze the cause-and-effect relationship of policies on the number of investment instruments, gold prices, rupiah exchange rates and costs of organizing the Hajj on the results of Hajj financial investments in Indonesia.This research uses a population, namely the financial reports of the Hajj Financial Management Agency (BPKH) of the Republic of Indonesia in the 2018-2022 period. Sampling in this research used the saturated sampling method. Hypothesis testing applies the Pearson product moment method using the Eviews tool. The research results show that the variable number of investment instruments has a very strong and significant correlation with the investment results of Hajj funds. The gold price variable has a strong and significant correlation with the investment results of Hajj funds. The exchange rate variable has a very low and insignificant correlation with the investment results of Hajj funds. The variable cost of organizing the Hajj pilgrimage has a moderate and significant correlation with the investment results of Hajj funds. Keywords: Number of Investment Instruments, Gold Price, Rupiah Exchange Rate, Cost of Organizing the Hajj Pilgrimage, Hajj Financial Investment Results